2019
DOI: 10.1126/science.aax0364
|View full text |Cite
|
Sign up to set email alerts
|

Structural mechanism of a Rag GTPase activation checkpoint by the lysosomal folliculin complex

Abstract: The tumor suppressor folliculin (FLCN) enables nutrient-dependent activation of the mechanistic target of rapamycin complex 1 (mTORC1) protein kinase via its guanosine triphosphatase (GTPase) activating protein (GAP) activity toward the GTPase RagC. Concomitant with mTORC1 inactivation by starvation, FLCN relocalizes from the cytosol to lysosomes. To determine the lysosomal function of FLCN, we reconstituted the human lysosomal FLCN complex (LFC) containing FLCN, its partner FLCN-interacting protein 2 (FNIP2),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
170
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 130 publications
(189 citation statements)
references
References 71 publications
10
170
0
4
Order By: Relevance
“…Cells in the -AA condition were transferred to imaging buffer (10 mM HEPES, pH7.4, 136 mM NaCl, 2.5 mM KCl, 2 mM CaCl 2 , 1.2 mM MgCl 2 ) and cells in the +AA condition were transferred to imaging buffer supplemented with amino acids, 5 mM glucose, and 1% dialyzed FBS (+AA) and imaged by spinning-disk confocal microscopy. Lysosomal enrichment was scored as described 31 using a home-built Matlab script to determine the lysosomal enrichment of GFP SMCR8. The score was analyzed for at least ten cells for each condition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells in the -AA condition were transferred to imaging buffer (10 mM HEPES, pH7.4, 136 mM NaCl, 2.5 mM KCl, 2 mM CaCl 2 , 1.2 mM MgCl 2 ) and cells in the +AA condition were transferred to imaging buffer supplemented with amino acids, 5 mM glucose, and 1% dialyzed FBS (+AA) and imaged by spinning-disk confocal microscopy. Lysosomal enrichment was scored as described 31 using a home-built Matlab script to determine the lysosomal enrichment of GFP SMCR8. The score was analyzed for at least ten cells for each condition.…”
Section: Methodsmentioning
confidence: 99%
“…The structure of the complex places it in the same class of heterodimeric longin-DENN domain protein GAP complexes as FLCN-FNIP 31,32 . FLCN-FNIP is a major node for communicating lysosomal nutrient status to the nucleus by virtue of its regulation of the RagC GTPase 34 and the phosphorylation of transcription factors regulating lysosome biogenesis and autophagy 31 . These data show how C9orf72 is stabilized on the lysosome in amino acid starvation by bridging contacts made by SMCR8 to WDR41.…”
Section: Mainmentioning
confidence: 99%
“…The loss of FLCN inhibits the phosphorylation of transcription factors TFEB and TFE3, promoting their nuclear translocation and activating lysosome biogenesis (Hong et al, 2010;Martina et al, 2014). Supporting this notion, structure-function analysis have suggested that the role of FLCN in regulating TFEB and TFE3 localization is dependent on the GAP activity of FLCN toward RagC (Lawrence et al, 2019), whereas immunoblotting assays in mammalian and nematode cells suggested that the loss of FLCN drives TFEB and TFE3 nuclear localization independently from the canonical mTORC1 pathway (El-Houjeiri et al, 2019). On the other hand, FLCN-deficient human cells appear to have impaired autophagosome maturation , suggesting a role for FLCN in autophagy regulation, which has also been reported during studies of the AMPK-FLCN functional relationship (see Section "A Potential Interaction of FLCN-FNIP With AMPK").…”
Section: The Flcn Complex Acts As the Intersection Between Nutrient Smentioning
confidence: 93%
“…A structural comparison between the GATOR1 and FLCN-FNIP complexes, combined with GTPase assays, led to the identification of FLCN-Arg164 as the catalytic residue exerting the GAP activity toward RagC, as mutations affecting this residue reduced the nucleotide exchange rate 100-fold (Lawrence et al, 2019;Shen et al, 2019). However, this residue is pointing away from the RagC nucleotide binding site, thus explaining the lack of GAP activity when FLCN is recruited to the lysosome under nutrient-starved conditions (Figure 4B, inset).…”
Section: The Structural Organization Of the Flcn-fnip Complex And Itsmentioning
confidence: 99%
See 1 more Smart Citation